“Downcast Eyes” on a “Downward Path to Wisdom”: Reading Milton’s “Darkness Visible” through a Derridean Perspective - Andrade, Miriam Piedade Mansur (Em Tese, 2007)
A reading of the visual metaphors of Paradise Lost will provethat the dialectics of traditional philosophy on the issue ofvision/blindness should be placed “under erasure”. The above mentioned operation is accomplished in the epic through a “darkness visible” perspective in the establishment of an(in)stance in the matters of interpretation.